Endometrial ablation for treatment of heavy menstrual bleeding: For whom it may not work? - Mamdouh M Shaaban; Ali M El Saman; Ahmed I Hasanein; Sherif A Shazly (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2019)
Endometrial Ablation (EA) refers to a group of minimally invasive approach that produces irreversible destruction of the endometrium. These procedures provide a satisfactory alternative to hysterectomy when medical treatment is contraindicated or unsatisfactory. While EA has become longstanding in practice, variable failure rates were reported, that seem to relate, in part, to time since intervention. Identifi cation of predictors of long-term outcomes allows better patient selection and lowers the probability of reintervention.This review discusses determinants of EA failure and how to improve patient selection based on available evidence.